Maintenance of Functional CD57+ Cytolytic CD4+ T Cells in HIV+ Elite Controllers - Phetsouphanh, Chansavath; Aldridge, Daniel; Marchi, Emanuele; Munier, C. Mee Ling; Meyerowitz, Jodi; Murray, Lyle; Van Vuuren, Cloete; Goedhals, Dominique; Fidler, Sarah; Kelleher, Anthony; Klenerman, Paul; Frater, John (Frontiers in Immunology, 2019)
Cytolytic CD4+ T cells play a prominent role in chronic viral infection. CD4+ CTLs clones specific for HIV-1 Nef and Gag are capable of killing HIV-1 infected CD4+ T cells and macrophages. Additionally, HIV-specific cytolytic CD4+ T cell responses in acute HIV infection are predictive of disease progression. CD57 expression on CD4s identifies cytolytic cells. These cells were dramatically increased in chronic HIV infection. CD57 expression correlated with cytolytic granules, granzyme B and perforin expression. They express lower CCR5 compared to CD57– cells, have less HIV total DNA, and were a minor component of the HIV reservoir. A small percentage of CD57+ CD4+ CTLs from EC were HIV-specific, could upregulate IFNγ with Gag peptide stimulation, express cytolytic granule markers and maintain TbethighEomes+ transcription factor phenotype. This was not observed in viraemic controllers. The maintenance of HIV-specific CD4 cytolytic function in Elite controllers together with CD8 CTLs may be important for the control of HIV viraemia and of potential relevance to cure strategies.